Maurits Ebben, Margriet Lacy-Bruijn, and Rolof van Hövell tot Westerflier (eds.), Alba: General and Servant to the Crown - José Eloy Hortal Muñoz (BMGN: Low Countries Historical Review, 2015)
Maurits Ebben, Margriet Lacy-Bruijn, and Rolof van Hövell tot Westerflier (eds.), Alba:  General and Servant to the Crown (Rotterdam: Karwansaray publishers, 2013, 464 pp., isbn 978 94 90258 08 5).